Fostering Coherence in Finnish Teacher Education: The MAP Model - Metsäpelto, Riitta-Leena; Warinowski, Anu; Poikkeus, Anna-Maija; Mikkilä-Erdmann, Mirjamaija (Springer VS, 2025)
This chapter discusses the process of fostering coherence in teacher education in Finland through a teacher competence model: the Multidimensional Adapted Process Model of Teaching (Metsäpelto et al., 2022). Originally developed to facilitate nationally unified student selection for initial teacher education, the MAP model represents a collective interpretation of teaching quality made by an expert panel from seven Finnish universities organizing teacher education. It encompasses the current evidence base and prevailing discourses on what teachers ought to know and be able to do. In this chapter, we examine recent trends in the Finnish educational landscape and present the argument that the MAP model holds promise for enhancing aspects of coherence within teacher education in both respect to its goals, emphases and shared guidelines as well as its implemented curricula across different units. Additionally, we present findings from an analysis comparing the curricula of primary school teacher education programs (grades 1 to 6) in two universities, which provides evidence of systemic coherence. The chapter concludes by offering a critical reflection on the implications of adopting a generic teacher competence model for fostering coherence in teacher education.
Coherence in European Teacher Education : Theoretical Models, Empirical Studies, Instructional Approaches